STUDI FARMAKOGNOSTIK SERBUK JUS KULIT NANAS (Ananas comosus (L.) Merr) - Farobbi, Muhammad Iqbal; Pratama, Iman Surya; Hidayat, Lalu Husnul (School of Pharmacy Institut Teknologi Bandung, 2025)
Pineapple (Ananas comosus (L.) Merr) is plant that can be utilized as traditional medicine. Pineapple is used as remedy for constipation, nausea, hemorrhoids, flu, anemia, urinary tract disorders, and various skin diseases. In addition, pineapple peels are used as anthelmintic. Pineapple peel has many therapeutic effects, but there is no pharmacognostic standardization related to pineapple peel to verify its validity and effectiveness. Purpose of this research is to evaluate various pharmacognostic parameters, such as organoleptic, botanical, and physical aspects of pineapple peel. This research conducted organoleptic, microscopic, specific gravity, pH, water-soluble and ethanol-soluble extract content, acid number, and fluorescence tests. This research produced organoleptic profile pineapple peel solution with brownish-yellow color, characteristic pineapple aroma, and sour taste. Microscopic observations revealed parenchyma, vascular bundles, meristematic cells, raphide calcium oxalate crystals, epidermis, stone cells, phloem, and fibers. Specific gravity of pineapple peel powder is 1.04 g/mL. pH of extract at 1% and 10% concentrations is 5 and 4. Water-soluble and ethanol-soluble content is 7.4 ± 0.23% and 5.3 ± 0.17%. Acid number of pineapple peel juice powder is 26.37 mg KOH/g. Pineapple peel juice powder fluoresces upon the addition of DMSO, ether, water, glacial acetic acid, petroleum ether, chloroform, toluene, acetic acid, dichloromethane, and ethyl acetate reagents